Evaluation of edge transport and core accumulation of tungsten for CFETR with EMC3-EIRENE and STRAHL. (1st December 2022) - Liu, B.; Dai, S.Y.; Yang, X.D.; Chan, V.S.; Ding, R.; Zhang, H.M.; Feng, Y.; Wang, D.Z.
Abstract: The edge transport and core accumulation of tungsten (W) particles on China Fusion Engineering Test Reactor (CFETR) have been studied by integrated modelling consisting of EMC3-EIRENE and STRAHL codes. The edge transport and power dissipation of W particles are simulated by EMC3-EIRENE. An in–out asymmetry of W (1–28)+ ions density has been revealed in the in- and out-board divertor regions. This is mainly due to the stronger reversal flow velocity of W ions at the outboard divertor. The upward flow of W ions near the separatrix leads to a moderate W impurity leakage from the divertor on CFETR compared to the existing full W device ASDEX Upgrade due to the high plasma density near the CFETR divertor targets. Further, the density distribution and radiation loss of W ions in the core region are investigated by STRAHL code. The high charge-state W (29–60)+ and W (61–74)+ ions mainly reside in the regions of ΨN = 0.20–0.98 and 0.00–0.90 (ΨN is the normalized poloidal magnetic flux), respectively. The W induced energy dissipation in different regions is assessed according to both STRAHL and EMC3-EIRENE simulations. Particularly, the impacts of the W core radiation on the operation regime are discussed according to the H-mode threshold scaling law proposed by Martin et al (2008 J. Phys.: Conf. Ser. 123 012033) for the baseline plasma on CFETR. Further, parameter studies on the pinch velocity ( v imp ) and diffusion coefficient ( D imp ) have been performed to check their impacts on the operation regime of CFETR. A three-fold increase of v imp / D imp results in a higher W core energy loss, which can lead to the transition from H-mode back to L-mode.